2012
DOI: 10.1007/s10509-012-1147-x
|View full text |Cite
|
Sign up to set email alerts
|

Viscous-resistive ADAF with a general large-scale magnetic field

Abstract: We have studied the structure of hot accretion flow bathed in a general large-scale magnetic field. We have considered magnetic parameters β r,ϕ,z [= c 2 r,ϕ,z /(2c 2 s )], where c 2 r,ϕ,z are the Alfvén sound speeds in three direction of cylindrical coordinate (r, ϕ, z). The dominant mechanism of energy dissipation is assumed to be the magnetic diffusivity due to turbulence and viscosity in the accretion flow. Also, we adopt a more realistic model for kinematic viscosity (ν = αc s H), with both c s and H as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Perhaps this result arises from considering a purely toroidal magnetic field. Although Abbassi & Mosallanezhad (2012) studied the effect of other field components on the dynamics of resistive ADAFs, the role of outflows was neglected in their work. In the present paper, we shall extend the work of Faghei & Mollatayefeh (2012) by considering other field components.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps this result arises from considering a purely toroidal magnetic field. Although Abbassi & Mosallanezhad (2012) studied the effect of other field components on the dynamics of resistive ADAFs, the role of outflows was neglected in their work. In the present paper, we shall extend the work of Faghei & Mollatayefeh (2012) by considering other field components.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zahra Zeraatgari et al (2018) showed that the ohmic resistivity in such flows modifies the amount of magnetic field and the role of the magnetic field in transferring angular momentum. Abbassi and Mosallanezhad (2012) also showed that the rotational velocity of the resistive accretion flows in the absence of outflow depends on the magnetic diffusivity. They found that the effect of magnetic diffusivity on the rotational velocity depends on the field components (see also Ghoreyshi 2020).…”
Section: Introductionmentioning
confidence: 90%
“…Hence, we assume that the anomalous magnetic diffusivity η can be expressed in the same way as in Bisnovatyi-Kogan and Ruzmaikin (1976), namely, η = η 0 c s H, where the α-prescription of Shakura and Sunyaev (1973) is adopted and the magnetic diffusivity parameter η 0 is a constant, less than unity. Note that this form of the magnetic diffusivity was used in some previous work (e.g., Shadmehri 2004;Abbassi and Mosallanezhad 2012;Samadi et al 2014), although H was replaced by c s /Ω K in the definition of η.…”
Section: Basic Equationsmentioning
confidence: 99%
“…Based on the self-similar assumption, many analytical works have also been done to investigate the structure and properties of hot accretion flow in one-dimension (e.g. Blandford & Begelman 1999;Akizuki & Fukue 2006;Abbassi et al 2008;Zhang & Dai 2008;Bu, Yuan & Xie 2009;Mosallanezhad et al 2012, Abbassi & Mosallanezhad 2012aMosallanezhad et al 2013) and also in two dimensions (e.g. Narayan & Yi 1995a;Xu & Chen 1997;Blandford & Begelman 2004;Xue & Wang 2005;Tanaka & Menou 2006;Jiao & Wu 2011;Mosallanezhad et al 2014;Samadi & Abbassi 2016;Mosallanezhad et al 2016;Samadi et al 2017).…”
Section: Introductionmentioning
confidence: 99%